2010
DOI: 10.1128/ec.00314-09
|View full text |Cite
|
Sign up to set email alerts
|

A Trk/HKT-Type K + Transporter from Trypanosoma brucei

Abstract: The molecular mechanisms of K ؉ homeostasis are only poorly understood for protozoan parasites. Trypanosoma brucei subsp. parasites, the causative agents of human sleeping sickness and nagana, are strictly extracellular and need to actively concentrate K ؉ from their hosts' body fluids. The T. brucei genome contains two putative K ؉ channel genes, yet the trypanosomes are insensitive to K ؉ antagonists and K ؉ channelblocking agents, and they do not spontaneously depolarize in response to high extracellular K … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 55 publications
2
11
0
Order By: Relevance
“…By using the fluorescent probe 3,3’-dihexyloxycarbocyanine, however, it was found that salinomycin did not affect the membrane potential of bloodstream forms of T. brucei (data not shown). This observation is in agreement with previous findings that valinomycin also did not influence the membrane potential of trypanosomes, although the parasites are extremely sensitive to this ionophore [21]. …”
Section: Resultssupporting
confidence: 93%
“…By using the fluorescent probe 3,3’-dihexyloxycarbocyanine, however, it was found that salinomycin did not affect the membrane potential of bloodstream forms of T. brucei (data not shown). This observation is in agreement with previous findings that valinomycin also did not influence the membrane potential of trypanosomes, although the parasites are extremely sensitive to this ionophore [21]. …”
Section: Resultssupporting
confidence: 93%
“…Our results showed that LB2003 was unable to grow in a minimal medium containing 2 mM KCl (not shown), similar to the observation in a previous study (44). However, the defective growth of LB2003 in this medium could be rescued by coexpression of cabP and SPD_0076 but not by the vector control (Fig.…”
Section: Identification Of a C-di-amp Binding Protein In S Pneumoniaesupporting
confidence: 91%
“…In contrast, the existence of TRK or HAK transporters in eukaryotic organisms that differ from fungi and land plants seems to be infrequent, although TRK transporters have been reported in several species of Trypanosoma and Leishmania (Mosimann et al, 2010). BLAST searches using fungal TRK and HAK proteins as queries identified some TRK and HAK proteins from eukaryotes that were different from fungi and land plants.…”
Section: Inventory Of Fungal K + and Na + Uptake Systemsmentioning
confidence: 96%